The library of the dead - Huchu, T. L. (Huchu, T. L. Edinburgh nights ;, 2021)
Ropa dropped out of school to become a ghost talker, and she now speaks to Edinburgh's dead - carrying messages to the living - but when she learns someone is bewitching children she investigates and discovers an occult library, a taste for hidden magic, and a wealth of Edinburgh's dark secrets.